New species and records of Keilbachia Mohrig (Diptera, Sciaridae) from the Oriental region - Hippa, Heikki; Vilkamaa, Pekka (Zootaxa, 2007)
The following new species are described: Keilbachia adunca (Brunei), K. ancylonema (Malaysia, Selangor and Myanmar, Kambaiti), K. camptonema (Malaysia, Selangor), K. clinata (Malaysia, Sabah), K. mirabilis (Malaysia, Selangor and Pahang), and K. orthonema (Malaysia, Sabah). K. curvispina (Edwards), comb. nov., from Sumatra, is redescribed and a lectotype is designated. K. acerspina Mohrig, previously known from Nepal, is recorded from Myanmar, Kambaiti.